Spatial Effects And Externalities Of The Rivals’ Networks In Hungary - Jóna, György; Tóth, Tamás (Journal of Tourism, Sustainability and Well-being, 2017)
Empirical results of the concept of territorial capital suggest that the Hungarian regional economic development is defined by the coopetitive networks of small- and medium-sized enterprises (SMEs). Therefore, overall purpose of this paper is to scrutinize theoretically and empirically on one hand the structural characteristics of the Hungarian coopetitive networks of SMEs, on the other hand is to analyze effects of the networks of same firms on regional economic development. Altogether three Hungarian coopetitive networks of SMEs were found and analyzed longitudinally embracing 127 entrepreneurs thus 127 interviews and 127 questionnaires were conducted as well. Since the coopetitive networks of enterprises have territorial extension, the advanced methods of network science and spatial econometrics were combined. The key findings show that focal firm plays outstanding role in redistributing market information, organizing mutual transportation and guarantees robustness of the coopetitive networks. Finally, the coopetitive networks of SMEs determine significantly the new jobs creation and pay raise, in general, the accumulation of territorial capital at regional scale as well.